Maternal employment and happiness: the effect of non-participation and part-time employment on mothers' life satisfaction - Eva M. Berger (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In contrast to unemployment, the effect of non-participation and parttime employment on subjective well-being has much less frequently been the subject of economists' investigations. In Germany, many women with dependent children are involuntarily out of the labor force or in part-time employment because of family constraints (e.g., due to lack of available and appropriate childcare). Using data from the German Socio-Economic Panel (SOEP) Study, this paper analyzes the impact of involuntary familyrelated non-participation and part-time employment on mothers' life satisfaction. Controlling for unobserved individual fixed effects, I find that both the pecuniary effects (foregone earnings) and the non-pecuniary effects (psychological costs) are significantly negative. Compensating income variations reveal that the residual household income would have to be raised by 182 percent (157 percent/77 percent) in order to just offset the negative effect of not being able to work because of family constraints (of being in short/long part-time employment). Moreover, in terms of overall happiness among mothers, non-participation is revealed to be a more serious problem than unemployment.
Keywords: I31; J21; J22; 330; Subjective well-being; life satisfaction; labor force participation; part-time; maternal employment; work-family conflict; Mütter; Frauenerwerbstätigkeit; Teilzeitarbeit; Lebenszufriedenheit; Familie; Deutschland